2023
DOI: 10.1590/1413-785220233102e259371
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Outcomes of Older Patients Operated Due to Hip Fractures

Abstract: Objective: Evaluating clinical factors associated with mortality in older patients who underwent surgical correction of hip fractures. Methods: This observational and retrospective study analyzed the medical records of 67 patients (aged older than 60 years), both men and women, who underwent surgical correction of hip fractures from 2019 to 2020 at Hospital São Paulo. The following variables were analyzed: age, sex, presence of comorbidities, affected hip region, and trauma mechanism. Statistical analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…[4] Correa et al reported that longer length of stay (LOS) is associated with higher mortality, readmission, and increased medical costs in HF patients. [5] The prolonged LOS places a significant burden on clinical care and undermines the equitable distribution of medical resources. [6] Therefore, more attention should be paid to identifying LOS-related factors to strengthen HF management, promote patient recovery, and reduce LOS.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Correa et al reported that longer length of stay (LOS) is associated with higher mortality, readmission, and increased medical costs in HF patients. [5] The prolonged LOS places a significant burden on clinical care and undermines the equitable distribution of medical resources. [6] Therefore, more attention should be paid to identifying LOS-related factors to strengthen HF management, promote patient recovery, and reduce LOS.…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of T2DM is associated with an increased risk of death after hip fracture 15 , little has been published quantifying the risk of mortality after fracture surgery by combining elderly with T2DM as two risk factors. This study aims to investigate the clinical characteristics and 1-year all-cause mortality in elderly hip fracture patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%